PD‐1 Analysis on CD28−CD27− CD4 T Cells Allows Stimulation‐Independent Assessment of CMV Viremic Episodes in Transplant Recipients. Issue 12 (22nd October 2013) - Dirks, J.; Tas, H.; Schmidt, T.; Kirsch, S.; Gärtner, B. C.; Sester, U.; Sester, M.
Abstract Expression of the inhibitory receptor programmed death 1 (PD‐1) on cytomegalovirus (CMV)‐specific CD4 T cells defines a phenotype associated with CMV viremia in transplant recipients. Moreover, CD28−CD27− double negativity is known as a typical phenotype of CMV‐specific CD4 T cells. Therefore, the co‐expression of inhibitory receptors on CD28−CD27− CD4 T cells was assessed as a rapid, stimulation‐independent parameter for monitoring CMV complications after transplantation. Ninety‐three controls, 67 hemodialysis patients and 81 renal transplant recipients were recruited in a cross‐sectional and longitudinal manner. CMV‐specific CD4 T cell levels quantified after stimulation were compared to levels of CD28−CD27− CD4 T cells. PD‐1 and cytotoxic T lymphocyte–associated antigen 4 (CTLA‐4) expression on CD28−CD27− CD4 T cells were related to viremia. A percentage of ≥0.44% CD28−CD27− CD4 T cells defined CMV seropositivity (93.3% sensitivity, 97.1% specificity), and their frequencies correlated strongly with CMV‐specific CD4 T cell levels after stimulation (r = 0.73, p < 0.0001). Highest PD‐1 expression levels on CD28−CD27− CD4 T cells were observed in patients with primary CMV viremia and reactivation (p < 0.0001), whereas CTLA‐4 expression was only elevated during primary CMV viremia (p < 0.05). Longitudinal analysis showed a significant increase in PD‐1 expression in relation to viremia (p < 0.001), whereas changes in nonviremic patients were nonsignificant. In conclusion, increased PD‐1 expression on CD28−CD27− CD4 T cells correlates with CMV viremia in transplant recipients and may serve as a specific, stimulation‐independent parameter to guide duration of antiviral therapy.